Monocephalic Sternopagus Tetrapagus Tetrapus Dicaudatus Monstrosity in a Surti Buffalo: A Case Report - Borakhatariya, Devasee; Kandhani, Pravin; Chikhaliya, P.S.; Manvar, N.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Dystocia is the common sequel of foetal monstrosities. Teratologic abnormalities or developmental arrests of the ovum, embryo or foetus may result in death or malformations of the antenatal individual. The defect of conjoined twins is non-inherited teratologic, which arises from a single ovum due to incomplete division during the primitive stage development and is monozygotic. Number of factors being influenced by genetic and environmental conditions may cause development of conjoined twins. Various genetic factors were predicted to be responsible for the failure of the separation of twins after the 13th day of conception (Srivastava et al., 2008). They are most common in cattle but are seen rarely in sheep, pigs, dogs and cats and are exceedingly rare in horses.